Diagnostic Performance of Molecular Rapid Test in Establishing Diagnosis of MDR-TB - Nunung Dartini Wahyuningtyas; Osman Sianipar; Andaru Dahesihdewi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Tuberculosis (TB) is a global health problem and is the leading cause of morbidity and mortality in many developing countries. Multi Drug Resistant Tuberculosis (MDR TB) becomes one burden of health problems considering the high morbidity and mortality rates. Establishment of MDR TB diagnosis is still a challenge, related to the tools and methods used, while cultural examination as gold standard is expensive and takes a long time. This study aims to evaluate diagnostic performance of Molecular Rapid Test or MRT (GeneXpert) in establishing diagnosis of MDR TB using Mycobacteria Growth Indicator Tube (MGIT) culture as gold standard. Using a cross sectional design, this study involved 51 subjects, a total of 26 (51%) male and 25 (49%) female, adult patients suspected TB, treated at dr. Ario Wirawan Lung Hospital (RSPAW) Salatiga. Mean age 48.2 + 16.35 years, (17-79 years). The MRT for TB and MDR TB detection showed 13 and 7 true positives, 32 and 43 true negatives; obtained 68.4% and 87.5% Sensitivity, 100% and 100% Specificity, 100% and 100% Positive Predictive Value (PPV), 84.2% and 97.7% Negative Predictive Value (NPV), respectively. A specific analysis to diagnose MDR TB by MRT on TB patient groups showed 7 true positives, 0 false positives, 11 true negatives and 1 false negative; obtained 87.5% Sensitivity, 100% Specificity, 100% PPV and 91.7% NPV. For establishing diagnosis of MDR TB, MRT provides perfect specificity. One false negative MDR TB in MRT results is likely resistant to other than rifampicin.